2003
DOI: 10.1117/12.487978
|View full text |Cite
|
Sign up to set email alerts
|

Combined bispectrum-filtering techniques for radar output signal reconstruction in ATR applications

Abstract: In automatic target recognition applications, an important task is to obtain denoised signal signatures of the object. In this paper, the reconstruction of 1-D deterministic signals, for example, range profiles, corrupted by random signal shift and additive white Gaussian noise using 2-D bispectrum is considered. Combined bispectrum-filtering techniques based on smoothing the noisy bispectrum estimates by 2-D linear and nonlinear filters are proposed. It is shown that bispectrum estimates obtained by the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 14 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…As has been demonstrated in [21], filtering of the real and imaginary parts of the bispectrum is preferable to magnitude and phase bispectrum filtering. One can expect that filtering the real and imaginary parts of the Fourier spectrum recovered from the bispectrum can also be more effective than filtering the recovered magnitude and phase spectra.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…As has been demonstrated in [21], filtering of the real and imaginary parts of the bispectrum is preferable to magnitude and phase bispectrum filtering. One can expect that filtering the real and imaginary parts of the Fourier spectrum recovered from the bispectrum can also be more effective than filtering the recovered magnitude and phase spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Although, most papers on bispectrum analysis consider the high-SNR case [6], [18], the results presented in [11], [20], [21] have demonstrated that the bispectrum methods can be effectively used in the low-SNR case also.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our strategy is based on the application of such properties of triple correlation and bispectrum that are widely employed in digital signal processing for solving problems of the detection and recovery of non-Gaussian processes embedded in additive Gaussian noise for radar systems (Totsky et al, 2003), bispectrum-based signal reconstruction in noisy environments (Totsky et al, 2006), biomedical engineering (Nakamura, 1993), and many other applications (Nikias and Raghuveer, 1987).…”
Section: Introductionmentioning
confidence: 99%